From lay concepts to therapeutic itineraries: sociological study about mental suffering an mental illness - Alves, Fátima (2020)
Societies relate to madness in accordance with their dominant concepts about the world. Modern rationality has created mental illness as an ‘object’ controlled by medicine. In lay knowledge the concepts, attitudes and practices associated with mental illness are culturally distant from the scientific representation of the body, the disease and the patient. The ‘semi-peripheral condition of Portuguese society’ allows us to believe that inside the more universal system of modernity, the explanation of insanity and mental illness in Portuguese society contains modern and traditional elements. This study focuses on lay knowledge about mental suffering and mental illness. Besides dominant explanations and interpretations, besides professions and politics, what are the lay conceptions and interpretations? Results show that the concept of mental illness recognises the term “illness” (there are ill people) but it always rejects it (mental suffering is not illness). Lay narratives refer to ‘ill people’ and not to ‘illnesses’, placing the nosologic holistic entity before the disease. Those rationalities categorise people in three ways: ‘ill-people’, ‘weak-people’ (these may turn into ill-people) and strong-people (these ones succeed in the combat with mental suffering, a normal event during life). Social representations emphasise a biomedical instead of psychodynamic model. ‘Talking’ is the most valued therapeutic resource. This represents a culture of resistance to psychiatrisation (medicalisation) of mental suffering. Mental illness narratives (concerning ‘the others’) and mental suffering narratives (concerning the self) represent a confrontation with the self and its identity. Illness and non-illness are entities allowing individual construction or destruction. Briefly, this research found that lay relationship with mental illness is made of diverse, complex and multiple logics. It proposes the concept of lay rationalities, in plural – lay rationalities about mental suffering and illness are not exclusively modern, they are plural.